Hemoglobin C trait accentuates erythrocyte dehydration in hereditary xerocytosis. Issue 8 (25th January 2017) - Yang, Elizabeth; Voelkel, Erin B.; Lezon‐Geyda, Kimberly; Schulz, Vincent P.; Gallagher, Patrick G.
Abstract: A 17‐year‐old male presented with acute hemolysis with stomatocytosis, elevated mean corpuscular hemoglobin concentration (MCHC), and osmotic gradient ektacytometry consistent with marked erythrocyte dehydration. Erythrocytes from both parents also demonstrated evidence of dehydration with elevated MCHC and abnormal ektacytometry, but neither to the degree of the patient. Genetic studies revealed the patient had hereditary xerocytosis (HX) due to a novel PIEZO1 mutation inherited from his mother and hemoglobin C (HbC) trait inherited from his father. HbC trait accentuated the erythrocyte dehydration of HX. Coinheritance of interrelated disorders and/or modifier alleles should be considered whenever severe erythrocyte dehydration is observed.